2021
DOI: 10.1111/imm.13351
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of IL‐7/IL‐7R signalling on the osteoimmunological system: a potential therapeutic target for rheumatoid arthritis

Abstract: The IL‐7/IL‐7R pathway plays a vital role in the immune system, especially in the inflammatory response. Monocytes/macrophages (osteoclast precursors) have been recently recognized as important participants in the osteoclastogenesis of rheumatoid arthritis (RA) patients. Here, we aimed to investigate the therapeutic potential of IL‐7/IL‐7R pathway in RA and to determine whether it could restrain osteoclastogenic functions and therefore ameliorate RA. Firstly, collagen‐induced arthritis (CIA) mice were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…This leads to the generation of in ammatory microenvironment, initiating and promoting the development of RA [43]. Hence, IL-7 is considered as a new therapeutic target [5,[43][44][45]. Our research once again provides theoretical support for these perspectives about IL-7 (OR = 1.23, 95%CI = 1.05-1.43, p = 0.009, FDR = 0.195).…”
Section: Discussionsupporting
confidence: 59%
“…This leads to the generation of in ammatory microenvironment, initiating and promoting the development of RA [43]. Hence, IL-7 is considered as a new therapeutic target [5,[43][44][45]. Our research once again provides theoretical support for these perspectives about IL-7 (OR = 1.23, 95%CI = 1.05-1.43, p = 0.009, FDR = 0.195).…”
Section: Discussionsupporting
confidence: 59%
“…The binding of IL7 ligand to IL7R activates two main pathways including the Janus kinase (JAK)/signal transducers and activator of transcription (STAT) and phosphoinositide-3 kinase (PI3K)/Akt, leading cell survival and development 36 , 37 , 47 , 49 51 . Notably our scRNA-seq data suggest that JAK/STAT signaling pathway is enriched at the early stage of RANKL-induced osteoclastogenesis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, recent studies indicate that JAK/STAT inhibitors, such as tofacitinib, significantly moderate the symptoms of rheumatoid arthritis and reduce the progression of osteoclasts as well as structural joint damage 57 . Moreover, it was reported that IL-7 contributes to inflammation and tissue destruction in patients with rheumatoid arthritis in a unique manner 37 and the blockade of IL-7/IL-7R signaling pathway protected collagen-induced arthritis (CIA) mice from bone degradation 51 . Taken together, these results support the therapeutic role of Notch1/IL7R axis in osteoclast-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have suggested that the IL-7/IL-7R pathway has dual regulatory effects on osteoclasts. As a bone growth factor, IL-7 promotes osteoclast differentiation by increasing the expression of RANKL, a key T cell source; however, IL-7 blocks osteoclast differentiation by directly inhibiting the STAT5 pathway in the RANKL-induced system [ 81 , 82 ]. IL-7 may also suppress the bait receptor of RANKL, OPG to promote osteoclastogenesis and mediate estrogen-induced bone loss [ 83 ].…”
Section: Myokines and Bone Metabolismmentioning
confidence: 99%